Les types de microconcertations et les gestes professionnels d’ajustement en contexte de co-enseignement intensif au Québec - Philippe Tremblay (Éducation et Socialisation)
In the context of research on intensive co-teaching settings in secondary education, observations made in class made it possible to identify 164 micro-consultations between co-teachers, i.e. times when the two teachers meet in class, during the action, to discuss various subjects. Using the notion of adjustment (Bucheton, 2009) to analyze the adaptation of the teacher to his class from the model of professional gestures in a co-teaching situation (Saillot and Malmaison, 2018), the objective of this article is to identify, categorize and analyze the different types of micro-consultations that take place during periods of co-teaching. This article presents a typology of ten types of micro-consultations : feedback ; planification ; coordination ; regulation ; modification ; validating ; correction ; verification ; evaluation and finally, the discussion.